The relationships between the levers of control, employee performance and banking performance - Hernando, Riski; Prasetyo, Eko; Yuli Sari, Rizki; Abdurrahman, Rezi (Jurnal Paradigma Ekonomika, 2024)
This study aims to examine the direct and indirect effect of the relationship between the influence of levers of control and employee performance on banking performance. The population of this study is all employees of Bank 9 Jambi with a total of 657 employees. The sample selection method in this study used purposive sampling. So, the sample that could be used was 73 respondents. The research model was tested using SEM-PLS with Warp PLS software version 7.0 which is a multivariate analysis technique to test the structural model. The main purpose of using this method is to analyze a predictive causality in which the problem is explored in a complex manner and theoretical knowledge is still scarce. The results showed that levers of control were able to directly influence employee performance and also directly influence banking performance. Meanwhile, employee performance is not able to influence banking performance. However, employee performance is not able to mediate the relationship between the influence levers of control on banking performance. These results reflect that the banking industry has been innovating in performance appraisal. This research becomes a guideline for company leaders to use multiple performance measurement systems in influencing employee performance and using levers of control in these relationships to improve performance.